Mitford on the causes of the Peloponnesian War - N.A. Yasnitsky (Ученые записки Казанского университета: Серия Гуманитарные науки)
This historiographical paper discusses the causes of the Peloponnesian War as understood by W. Mitford, an English historian at the turn of the 18th – 19th centuries. His work “The History of Greece” was considered the most influential until the publication of “History of Greece” by G. Grote. It was found that W. Mitford’s interpretations were differently assessed in the 19th – 20th centuries: he was accused of political bias, praising Sparta, and criticizing democracy in general and the Athenian system of government in particular. The evidence that W. Mitford’s interpretations of the causes of the Peloponnesian War are based on the same objective factors as that ones introduced by modern scholars: not on his personal preferences or political views, but on the analysis of the political situation in Greek states based on the material interests of the political groups in democratic Athens imposing its rule to other Greek States in order to satisfy these interests.